Biomimetic astrocyte cell membrane-fused nanovesicles for protecting neurovascular units in hypoxic ischemic encephalopathy - Zihao Liu; Qian Xia; Chanyue Wang; Jiacan Xu; Kangqian Tian; Zhihai Wang; Longji Li; Yuchen Li; Hao Shang; Qian Liu; Tao Xin (Journal of Nanobiotechnology)
Abstract Hypoxic ischemic encephalopathy (HIE) refers to neonatal hypoxic brain injury caused by severe asphyxia during the perinatal period. With a high incidence rate and poor prognosis, HIE accounts for 2.4% of the global disease burden, imposing a heavy burden on families and society. Current clinical treatment for HIE primarily focuses on symptomatic management and supportive care. Therefore, the developments of effective treatment strategies and new drug formulations are critical for improving the prognosis of HIE patients. In order to protect the compromised neurovascular units after HIE, we prepared membrane-fused nanovesicles for delivering rapamycin and si EDN1 (TRCAM@RAPA@si EDN1). Due to the homotypic targeting feature of membrane-fused nanovesicles, we employed astrocyte membranes as synthetic materials to improve the targeting of astrocytes in brain while reducing the clearance of nanovesicles by circulatory system. Additionally, the surface of cell membrane was modified with CXCR3 receptors, enhancing the homing of nanovesicles to infarcted lesions. Lipid vesicles were modified with TK and RVG29 transmembrane peptides, enabling responsive release of internal drugs and blood-brain barrier penetration. Internally loaded rapamycin could promote protective autophagy in astrocytes, improve cellular oxidative stress, while si EDN1 could reduce the expression level of endothelin gene, thereby reducing secondary damage to neurovascular units. Graphical Abstract